Setting the Agenda: Jean Royce and the Shaping of Queen's University - Kinnear, Mary (Labour / Le Travail, 2004)
The article reviews the book, "Setting the Agenda: Jean Royce and the Shaping of Queen's University," by Roberta Hamilton.